2020
DOI: 10.1093/ageing/afaa100
|View full text |Cite
|
Sign up to set email alerts
|

Does the public feel prepared to be substitute decision-makers? Gaps in preparedness and support for a high school curriculum: a national survey

Abstract: Background Substitute decision-makers (SDMs) make decisions on behalf of patients who do not have capacity, in line with previously expressed wishes, values and beliefs. However, miscommunications and poor awareness of previous wishes often lead to inappropriate care. Increasing public preparedness to communicate on behalf of loved ones may improve care in patients requiring an SDM. Methods We conducted an online survey in Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…12 There is misunderstanding among the public of the benefits and harms of treatments during serious illness such as cardiopulmonary resuscitation 13 and palliative care 14 and a lack of understanding of the SDM role. 15 These common misunderstandings that undermine successful ACP likely contribute to the decisional conflict and regret experienced by some SDM. 16 The novel decision aid, (the Plan Well Guide tool; www.…”
mentioning
confidence: 99%
“…12 There is misunderstanding among the public of the benefits and harms of treatments during serious illness such as cardiopulmonary resuscitation 13 and palliative care 14 and a lack of understanding of the SDM role. 15 These common misunderstandings that undermine successful ACP likely contribute to the decisional conflict and regret experienced by some SDM. 16 The novel decision aid, (the Plan Well Guide tool; www.…”
mentioning
confidence: 99%
“…The educational workshop intervention in this study illustrated statistically significant improvements in LTC staff’s knowledge and comfort in implementing a palliative approach to care and their perceptions toward ACP conversations. Currently, in Canada, the LTC system is not structured effectively to have these ACP conversations early in the disease trajectory ( Siu et al, 2020 ; Wong et al, 2021 ). Earlier ACP can potentially mitigate future family conflicts or poor care decisions ( Andreasen et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, few participants reported accessing support to help them make these decisions, which highlights a potential need to develop resources addressing the types of challenges SDMs are likely to encounter and for this content to be delivered in ways that are preferable for potential SDMs. Findings from a recent survey among the Canadian general population showed that most participants would support the introduction of a curriculum for senior high school students to learn about being an SDM, 31 further highlighting the need to develop and evaluate interventions that address the problem of a lack of preparedness to be an SDM in the general public. 44 In our study, a majority of participants preferred to obtain information from a health professional.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a recent national survey of Canadians examining preparedness to act as an SDM showed that while 25% of the sample had previous experience as an SDM and 71% believed they would have to act as an SDM in the future, 62% believed they understood the SDM role and only 53% felt prepared to be an SDM. 31 The authors are not aware of additional similar studies exploring the general public's knowledge and preparedness for the SDM role. However, observational studies from the USA suggest being an SDM is associated with elevated levels of anxiety and depression in some people 32 and that a person's confidence to be an SDM varies substantially, with people who have previous SDM experience or greater communication with the patient's doctor demonstrating increased confidence levels compared with those who do not.…”
Section: What Is Their Significance?mentioning
confidence: 99%